Review Artikel : Pelaksanaan Telefarmasi Pada Pelayanan Kefarmasian Di Farmasi Komunitas - Firda Riska Rahayu; Iqbal Sujida Ramadhan; Rini Hendriani (Journal of Pharmaceutical and Sciences, 2023)
During the 21st of century, the use of information technology and telecommunications is proliferating, including in the healthcare sector. One of the health services is telepharmacy. Telepharmacy is a relatively new concept, so research is needed to optimize the application of telepharmaceuticals. Based on that, this article explains the implementation of telepharmacy in various countries and the advantages and limitations of telepharmacy. The methods were carried out by searching electronically through Google scholar, Pubmed, ScienceDirect, and NCBI. A total of 24 journals and three regulations fulfilled the inclusion criteria. This review shows that telepharmacy has been carried out in many countries, such as in Asia, Europe, America and Africa. The form of implementation is different by each country, for example, through a platform, video conferencing, chat messenger and telephone. In addition, to the advantages, several challenges involve cooperation between patients, the government and private sectors, as well as academic institutions, which is essential for achieving appropriate results and effectively improving health services.